Evaluation of User Satisfaction in Electronic Service Manuscripts (TNDE) Using PIECES Framework Analysis - Reza Hikmatulloh; Qurrotul Aini; Muhammad Qumarul Huda; Evy Nurmiati; Nida’ul Hasanati (Sistemasi: Jurnal Sistem Informasi, 2022)
Official documents as a result of the Ministry of Public Works and Public Housing (PUPR) of the activities are increasing in quantity, therefore, to handle this needs to be backed up with a capable administrative system, namely: a computerized system to be more efficient and effective in managing official documents that called the System Electronic Service Manuscripts (TNDE) at the Ministry of PUPR. However, many users when accessing the TNDE system, often experience problems. The average user has experienced slow processing (loading) when the system is being accessed. The problem usually lies in the server network that does not respond, hence it interferes with the running of the system. The authors investigate user satisfaction on TNDE system using the PIECES framework to 74 respondents. The results of the analysis state that the average value in the Performance domain is 3.82, Information and data is 3.93, Economic is 4.18, Control and Security is 3.49, Efficiency is 4.09, and Services is at a score of 3.9. This indicates that the user is satisfied in using TNDE system.